Accuracy of eGFR Equation for Predicting Glomeruloar Filtration Rate in Potential Living Kidney Donor (Pakistan Journal of Kidney Diseases, 2024)
This Descriptive Cross-Sectional Study, involving 201 patients, conducted at Sindh Institute of Urology and Transplantation (SIUT) Karachi, Pakistan after approval from institute research board. The estimated Glomerular Filtration Rate (eGFR) was calculated using the appropriate equation. Participants were instructed to collect their urine over a 24-hour period in a container devoid of any additives or preservatives. The collected urine specimens were subsequently sent to the institutional laboratory for analysis, with GFR determined based on 24-hour urine creatinine clearance to ensure accuracy. All data collected during the study period were meticulously entered into a predefined proforma, which was then electronically stored and utilized for research purposes.Results: Mean ± SD of age was 33.30±9.12 years. Out of 201 patients, 124 (61.7%) were male while 77 (38.3%) were female. In distribution of accuracy of eGFR by CKD-EPI equation, accuracy of (Cr-Cys) equation was noted as 60 (29.9%), (Cys) as 47 (23.4%) while accuracy of CKD- EPI (PK) equation was documented as 96 (47.8%).Conclusion: It is to be concluded that accuracy of CKD-EPI is closer to 24 -h urinary creatinine clearance in the calculation of eGFR. However, none of the eGFR formulas can be used in renal transplant donors because of their low accuracy, and 24-h urine creatinine clearance should be used for evaluation of the GFR in this population.
Keywords: End stage kidney disease; chronic kidney disease; eGFR; CKD-EPI; Risk assessment; 24 hour urine creatinine clearance